Comparative efficacy and safety of Xuebijing injection as adjuvant therapy in sepsis-associated acute kidney injury: a systematic review and meta-analysis - Shu, Bofei; Zhou, Xu; Fan, Jing; Yang, Can; Deng, Wei; Fang, Bangjiang; Zhang, Huan (Frontiers in Pharmacology, 2025)
BackgroundXuebijing injection is a standardized traditional Chinese medicine formulation comprising extracts from safflower, red peony, Chuanxiong, Angelica, and Salvia miltiorrhiza. It is clinically employed for the treatment of sepsis and associated complications.MethodsThis systematic review evaluated the efficacy and safety of Xuebijing injection in treating sepsis-associated acute kidney injury (SA-AKI). Six databases were searched up to 1 September 2024, to identify randomized controlled trials (RCTs) comparing Xuebijing injection combined with conventional therapies versus the same conventional therapies alone. Data from individual RCTs were synthesized by meta-analysis, with effect measures expressed as risk ratios (RRs) or mean differences (MDs) and their 95% confidence intervals (CIs). Trial sequential analysis was used to assess the precision of the effect estimates, and the GRADE system was used to evaluate the quality of evidence.ResultsEighteen RCTs involving 1,650 patients were included. Meta-analysis demonstrated that, compared with conventional therapies alone, Xuebijing injection combined with conventional therapies significantly reduced 28-day mortality (RR 0.82%, 95% CI 0.69–0.98). It also significantly improved renal function (serum creatinine level: MD -17.55 μmol/L, 95% CI: −23.22 to −11.88; blood urea nitrogen level: MD -1.58 mmol/L, 95% CI -1.83 to −1.32; urine volume: MD 5.83 ml, 95% CI: 3.45–8.21), inflammatory cytokines (tumor necrosis factor-alpha level: MD -29.20 ng/ml, 95% CI: −39.15 to −19.25; interleukin-6 level: MD -25.80 ng/mL, 95% CI: −35.56 to −16.04; interleukin-10 level: MD -8.02 ng/mL, 95% CI: −13.98 to 2.07), and immune function (percentage of CD3+ T cells: MD 10.30%, 95% CI 7.77%–12.84%; percentage of CD3+ T cells: MD 9.57%, 95% CI 3.53%–15.61%; CD4/CD8 ratio: MD 0.27, 95% CI 0.18–0.36). In addition, Xuebijing injection significantly alleviated the severity of SA-AKI as measured by the Acute Physiology and Chronic Health Evaluation II score (MD -3.12, 95% CI: −4.51 to −1.73). Subgroup analyses suggested potential effect modifications based on treatment duration or dosage. All reported adverse reactions were mild.ConclusionXuebijing injection may help reduce mortality and improve renal function in patients with SA-AKI. However, the certainty of evidence ranged from moderate to very low, underscoring the need for validation through large-scale, double-blind randomized controlled trials.